The results of paleomagnetic studies of the Pleistocene deposits of the Azov Sea (the Botievo section) - Slivinskaya, G.V.; Skarboviychuk, T.V.; Yakuhno, V.I.; Knyazkova, I. L. (Geofizicheskiy Zhurnal, 2012)
A paleomagnetic study of Quaternary sedimentary rocks in seaside outcrops near the Botievo village from the Priazov area has been made. The standard procedure of the samples demagnetization by alternating magnetic field and temperature, the separation of the characteristic J0n component by the method of the Kirshvink analysis were used to acquire the initial data of further paleomagnetic constructions. Analysis of the received results allows to define the Matuyama-Brunhes boundary at the level of deposits of Martanosha stratigraphic horizon, we can find at least 12 reversed polarity intervals in Brunhes Chron and 3 normal polarity intervals in Matuyama Chron.